Placental malaria infection is associated with downregulation of STAT-6 and ANG-1 in decidual macrophages - Owino, Fred; Kijogi, Caroline; Anzala, Omu; Walong, Edwin; Jael, Obiero; Nyanjom, Steven G.; Eric, Agola Lelo; Kanoi, Bernard N.; Gitaka, Jesse (Frontiers in Immunology, 2025)
IntroductionMacrophages play a crucial immunological role in maintaining pregnancy. Placental malaria infection may cause dysfunction in decidual macrophages which then culminates in the associated pregnancy complications. Here, we determined the influence of placental malaria on decidual macrophages, by assessing their distribution based on their unique phenotypes, and examining their expression levels of transcription factors as well as angiogenic factors, in placentas from women living in a malaria-endemic area.MethodsWe compared these macrophage parameters in placentas from malaria infected women to those from the uninfected women. Placentas were collected upon delivery and malaria infection determined by histology together with PCR from dry blood spots obtained from placental blood. Following enzymatic dissociation of placental tissue, immune cells were enriched from the total population of placental cells by density centrifugation. Macrophage phenotypic characteristics were then analyzed from the placental immune cells by flow cytometry. The expression of surface markers CD68, CD80, CD86, CD163, CD206, and CD209, was used to delineate the macrophage populations. For gene expression profiling, macrophages were isolated from the placental immune cells and the expression level of transcription factors STAT-1, IRF-5, STAT-6, c-Maf and angiogenic factors ANG-1, ANG-2 and VEGF determined by qPCR.Results and DiscussionWe found no difference in the total macrophage populations and M1 and M2 macrophage profiles between uninfected and infected placentas, however, M2 macrophages were significantly higher compared to their M1 counterparts regardless of infection status. Notably, the gene expression levels of the transcription factor STAT-6 and angiogenic factor ANG-1 were significantly lower in infected placentas. These findings provide a basis for further understanding of the role of placental macrophages in placental malaria pathogenesis. Analysis of the functional consequences of these observations is needed to determine if these factors can be explored to reprogram macrophage polarization to desired state.